RECENT RECORD OF LEAST PIPISTRELLE (Pipistrellus tenuis) (VESPERTILIONIDAE: CHIROPTERA) FROM ISLAMABAD - A. Javid; M. Mahmood-ul-Hassan; M. Afzal; M. S. Nadeem; S. M. Hussain (Journal of Animal and Plant Sciences, 2012)
The Least Pipistrelle Pipistrellus tenuis (Temminck, 1840) was captured from northern Punjab first in 1926 and then in 1961. We captured two specimens of this species from the same area during a three years’ survey (2008-2011) to describe and compare their external body, cranial and bacular measurements with those available in literature. Mean body mass of the captured specimens was 4.25 ± 1.061 g, the head and body length was 35.00 ± 2.828 mm, the forearm was 28.00 ± 0.707 mm long. The greatest length of the skull was 10.19 mm and baculum was 3.46 mm long. Mean frequency of maximum energy of four pulses from two calls was 34.1 kHz and the calls were single harmonic. This paper also provides first hand information on the call parameters and status of this species from Pakistan.
Keywords: Least pipistrelle; Distribution; Baculum; Cranium; Forearm; kHz; Pakistan.